Diagnostic markers of early neonatal sepsis – limitations and perspectives - O. I. Ivanova; E. V. Grigoriev (Вестник анестезиологии и реаниматологии)
Neonatal sepsis continues to be one of the main problems in the treatment of premature infants due to the variability of the clinical signs, the lack of uniform diagnostic criteria, optimal markers that would not be affected by the course of pregnancy, gestational age, delivery, and the early neonatal period.The objective: to analyze current data on serum markers of neonatal sepsis in newborns including children with extremely low and very low birth weight.The article reviews traditional markers that are currently widely used in resuscitation neonatal practice – C-reactive protein, procalcitonin, and among the new ones – preadrenomedullin, and presepsin. It lists their positive and negative aspects, compares their characteristics, notes publications that describe the possibilities and limitations of their use for early diagnosis of neonatal sepsis.It has been concluded that among all markers, presepsin is of the greatest interest due to its highest sensitivity and specificity compared to the others.